Online customized printed t-shirt booking system - Yoong, Zhi Lin (2023)
In recent years, t-shirt customization has become a trend around the world. The T-shirt has become a powerful tool for self-expression and advertising, allowing individuals and organizations to convey their messages effectively. However, the current printed t-shirt customization booking practice face several challenges, such as communication error with retailers, time-consuming trips to physical stores for design and booking, and more. Therefore, an online customized t-shirt printed booking system was proposed to address these challenges. This project aims to create a web application that simplifies the entire process of customizing, printing and booking t-shirts online. The system includes features such as t-shirt customization, generation of t-shirt designs, a shopping cart, checkout process, t-shirt booking queries, stock management and booking management. This project solution was implemented using the React and Laravel frameworks for the front-end and back-end systems, respectively. The methodology used in the Software Development Life Cycle was Rapid Application Development. Three iterations of prototypes were created and refined to expedite coding during the construction phase. The developed systems were then conducted unit, integration, and user acceptance tests. A user acceptance result of 4 out of 5 was produced and demonstrated high user satisfaction with the systems. The implemented system successfully achieved its project objectives. Meanwhile, features such as AI-powered design generation and user interface of stock management still have room for improvement that is found in user acceptance testing.